Unusual severe cases of type 1 porcine reproductive and respiratory syndrome virus (PRRSV) infection in conventionally reared pigs in South Korea. Issue 1 (December 2015) - Lyoo, Kwang-Soo; Yeom, Minjoo; Choi, Jong-Young; Park, Jong-Hwan; Yoon, Sun-Woo; Song, Daesub
Abstract Background Porcine reproductive and respiratory syndrome virus (PRRSV) causes a loss of approximately US$ 70 million every year to the South Korean pork industry. There are two distinct genotypes: European (type 1) and North American (type 2). In South Korea, type 1 and type 2 PRRSV are widely distributed and have evolved continuously since the infection was first described. Here, we present two field cases of type 1 PRRSV infection with unusually severe pathogenicity. Case presentation The first case farm was a two-site production system comprising farrow-to-grower and grower-to-finish units and was historically free from PRRSV infections. The PRRSV vaccine had not been used in both units. In October 2014, pigs in the grower-to-finish unit experienced severe respiratory distress with the mortality rate reaching to 22 %. Despite antibiotic treatment, clinical signs were still noticed in most pigs. The second case farm was also a two-site production system, but had two separate farrow-to-grower units (unit A and unit B). Historically, type 1 PRRSV was continuously present in unit A, but unit B was free from PRRSV. Thus, all grower pigs of unit B were vaccinated before being moved to the grower-to-finish unit. In November 2014, severe respiratory distress was seen in pigs of the grower-to-finish unit. Significant respiratory distress was observed in only the grower herd moved from unit B, and the mortality of those pigs was ~50 %. However, no disease was shown in the grower pigs from unit A. Conclusions To our knowledge, the present study is the first observation of the cases of infection by highly pathogenic type 1 PRRSV in South Korea. The Korean type 1 PRRSV strains have undergone unique evolutionary dynamics for the last decade in this country. Although there are known to be three clusters of Korean type 1 PRRSV, their pathogenicity could not be categorized owing to their high level of genetic diversity. Therefore, further studies are needed to demonstrate the novel classification of Korean type 1 PRRSV strains according to their virulence factors.